Identification of novel proteins associated with the development of chemoresistance in malignant melanoma using two-dimensional electrophoresis - Sinha-von Jaschke, Pranav; Kern, Monika; Schnölzer, Martina; Schadendorf, Dirk (Electrophoresis, 2000)
A model system for studying chemoresistance in human melanoma cells (MeWo) has been established utilizing the four commonly used cytotoxic drugs vindesine, cisplatin, fotemustine and etoposide to yield stable drug-resistant sublines. We analyzed phenotypical differences between MeWo cells and their chemoresistant counterparts using two-dimensional electrophoresis. Proteins that were overexpressed in chemoresistant cell lines were purified and identified using matrix assisted laser desorption/ionization-time of flight — mass spectrometry (MALDI-TOF-MS) and microsequencing. Here we show that four proteins, namely the translationally controlled tumor protein, the human elongation factor 1-δ, tetratricopeptide repeat protein and the isoform 14-3-3-γ of the 14-3-3-family are overexpressed in chemoresistant melanoma cell lines. The significance of these findings is now being verified using transfection experiments with the aim of developing more effective chemotherapy protocols.